2011
DOI: 10.1590/s0366-69132011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Local structures and electronic band states of α−Fe2O3 polycrystalline particles in the glazes of the HIZEN celadons produced in the Edo period of Japan, by means of X-ray absorption spectra (II)

Abstract: HIZEN celadon glazes produced in 1630's to 1790's (Edo period, Japan) have been investigated by means of X-ray absorption spectra (XAS) near a Fe-K edge by using synchrotron radiation and a Mössbauer spectrum. The XAS suggest that the local structure around Fe 2 O 3 fine powders is slightly different between the Izumiyama ceramics of mainly the Quartz-SiO 2 and Ohkawachi ceramics of mainly the feldspar of (K,Na)Si 3 O 8 (Sanidine), and that the glazes of the HIZEN celadons include the Fe 2 O 3 fine powders in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…As reported in our other paper [21], we found that, for the HIZEN celadons, there is no chemical reaction from α-Fe 2 O 3 to FeO structure under the deoxidizing thermal treatment at high-temperature of about 1200 to1250 °C. Thus, in Table II, we analyzed the ion oxide as Fe 2 O 3 in the celadon glazes.…”
Section: +supporting
confidence: 85%
“…As reported in our other paper [21], we found that, for the HIZEN celadons, there is no chemical reaction from α-Fe 2 O 3 to FeO structure under the deoxidizing thermal treatment at high-temperature of about 1200 to1250 °C. Thus, in Table II, we analyzed the ion oxide as Fe 2 O 3 in the celadon glazes.…”
Section: +supporting
confidence: 85%
“…Usually, the raw celadon materials also include transitionmetal ions of Mn, Cr, Cu of very small amount in the glaze. The contained other transition-metal ions also affect sensitively the color and brightness of the celadon glaze, as like Fe [10,11]. However, it is not easy to detect the X-ray fluorescence of very weak emitted from the other transitionmetal ions by using the ordinary X-ray fluorescence analyzer, as Tables I and II. Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The celadon glaze changes gradually its color from yellow-brown to black color, as increasing the iron oxides under the deoxidizing thermal treatment [3]. Recently, we had been studying the glaze-color of the HIZEN celadons, called "Seiji", which were produced at Arita (north part in Kyushu island) in 1630's to 1790's (Edo period, Japan) [4][5][6][7][8][9], by means of the X-ray absorption spectra (XAS) near the Fe-K edge by using synchrotron radiation and the Mössbauer spectrum, in addition to the X-ray diffraction [10,11]. The results suggested that the glaze-colors of the HIZEN celadons depend on the material properties of the used raw ceramics and the other transitionmetal ions Cr, Cu, Zn of very small amounts, in addition to Fe 2 O 3 of small amounts.…”
Section: Introductionmentioning
confidence: 99%
“…It can complement the XRF commonly used in archaeometry [5], due to its sensitivity to structures of different phases [6]. Extended X-ray absorption fine structure (EXAFS) was successfully used in identifications of decorated Japanese and Sicilian ceramics, respectively based on Fe and Cu species in their coating [11,12]. In addition to the aforementioned Fe K-edge XANES, there were studies on other elements including Mn, Cu, Cr, As and S species in ancient ceramics and pigments [6,[12][13][14] and Mn K-edge XANES is also used in this study.…”
Section: Introductionmentioning
confidence: 99%